Perdagangan Perempuan Nepal ke India dan Peran Jejaring Feminis Transnasional - Yusuf Eko Suwarno, Fatma (Nation State: Journal of International Studies, 2020)
Nepal has faced high rates of woman trafficking to India for a long time. Various efforts were made but the rate did not decrease. This article intended to examine this phenomenon by examining the transnational feminist network (TFN), such as The Global Alliance Against Women Trafficking (GAAWT). GAAWT focuses on changes in the political, economic, social, legal system and structures related to the practice of trafficking in women by using a human rights approach to people who are regulated, non-discriminatory, uphold equality and uphold the principles of accountability, participation, and inclusiveness in the methodology, organizational structure and procedures. This study utilizes qualitative methods and transnational feminism theoretical framework. The result shows that GAAWT TFN has played a role in overcoming the issue of trafficking of Nepalese women to India by voicing the human rights of women in Nepal with a human rights approach. Even so, the trafficking of Nepalese women to India is still high. Therefore, evaluating approaches that pay attention to cultural aspects as well as various political identities at play can increase the effectiveness of TFN.